MENELUSURI PERAN DAN TANTANGAN PROGRAM GURU PENGGERAK DI SEKOLAH DASAR - Prasetyo, Teguh; Putria Gadies, Shelly; Wudda, Rikza Fauziyah; Talaar, Vania Salsabila (UHN IGB Sugriwa Denpasar, 2024)
Major challenges in education in Indonesia include the complexity of the curriculum, frequent changes, and the placement of teachers according to their expertise. To overcome this, the government launched the Teacher Mover in schools program as part of efforts to implement the independent learning curriculum. This program aims to obtain an overview of the implementation of the driving teacher program in schools regarding the role of the program, training activities, obstacles and benefits. Qualitative descriptive research was analyzed thematically with the help of the NVivo 12 application. The results focused on teachers' driving role as leaders in learning and creative teachers. The subfocus of training and mentoring activities found interesting indicators such as program evaluation, providing mentoring, managing the quality of activities, and solving program problems. Next, the subfocus of challenges and benefits will be discussed in depth in this scientific article.